Համակեդրոնացման ճամբարներու արտացոլումը երգ-երաժշտութեան մէջ - Գաթրճեան, Աւօ. Յ․ (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The article examines songs and music born in different languages a nd during different periods of the Armenian Genocide in the places of the Genocide camps, in the area of the Euphrates River. The themes of their compositions are various: inhumane events, geographical locations, descriptions of scenes, gatherings of orphans and orphanages, people, expression of feelings, and other creepy stuff. The musical style is diverse: folk, rock, heavy metal, rap, hip-hop, new-age, classical, jazz, etc., the areas reflecting the song- music are also artistic, graphic film series, documentary tapes, and plays. В статье представлены песни и музыка, родившиеся на разных языках и в разные периоды Геноцида армян в концентрационных лагерях, а также в районе реки Евфрат. Тематика их композиций разнообразна: бесчеловечные события, географические локации, описания сцен, сбор сирот и детские дома, отдельные люди, выражение чувств и т.д. Музыкальный стиль также разнообразен: фолк, ашугская музыка, рок, хэви-метал, рэп, хип-хоп, нью-эйдж, классика, джаз и другие направления, а также песенная музыка, отраженная в художественных фильмах и киносериалах, документальные ленты и т. д.
Keywords: Հայոց ցեղասպանութիւն